Alienation and Redemption: The Praxis of (Roman) Archaeology in Britain. Issue 1 (24th September 2019) - Weekes, Jake; Watson, Sadie; Wallace, Lacey; Mazzilli, Francesca; Gardner, Andrew; Alberti, Marta
The TRAC session that led to this series of combined mini-papers was consciously designed as a forum for discussion. The aim of the session was to consider ways to tackle perceived systemic problems in the archaeology of Roman Britain (and, by extension, in the archaeology of other periods) that lead to destructive methods, interpretive fallacies and poor job satisfaction. The shared feeling of those attending the TRAC session seemed to be that well established systems in developer-funded or 'commercial' archaeology, university archaeology departments and even in museum environments are overly driven by ideas of competition, division and acquisition for its own sake, the apparently dominant neoliberal values of our time. Such values promote constraining hierarchies within and between organisations, generating lack of communication and ineffective team working. In this 'manifesto'-style paper, different authors discuss the systemic issue that has most impact on their field of employment or research, and offer solutions for a potential 'redemption'.